5th residential college web site development / Goh Wei Meng - Goh, Wei Meng (2001)
This report was based on the final year project, as a partial requirement for the degree of Computer Science. This report includes topics on introduction to the project, review of literature and the methodology used in developing of this project. A view of the developing activities and schedules are also included. A list of references used in this project is also provided. Computer information system and computer applications are very important to all the organizations. Thus, the government launched the Electronic Government, which is one of the flagship applications of Multimedia Super Corridor (MSC) to lead the country into information Age. The Electronic Government will improve both how government operates internally as well as how it delivers services to public. It seeks to improve the convenience, accessibility and quality of interactions with citizens and business; simultaneously, it will improve information flows and process within government to improve the speed and quality of policy development, co-ordination and enforcement. In addition, Electronic Government will play an essential role in catalyzing the development of the MSC, as well as furthering the political and economic developments goals in Vision 2020. (Concept request for proposal, Electronic Government Flagship Application, Prime Minister's Office - Generic Office Environment, Malaysian Administrative Modernization and Management Planning Unit (MAMPU), Prime Minister's Department Malaysia, CRFP NO: MAMPU/EG/3/97. ) This project will focus on s" Residential College web site. The web site provides an easier way for the visitors to search for information about the college and also the residents staying there. As a result, this web site will give a lot of effort and benefit to the visitors, especially the outsiders. The functionality of the web site will grow as time goes to suit the environment. This report was intended to give an understanding to the reader about the activities done during the developing of this project and the way used in the development.